Draft Sixth Five Year Plan 1980-85 Vol II Tripura - Planning Commission (Planning Commission, 1980)
The area of the State is 10,477 Sq. Km. During 1978 the population was estimated to be approximately 19 lakhs. By 1985 the projected population may be about 23.5. lakhs or so. More than 76% of the working force depend on agriculture and allied sectors for livelihood .Because of conspicuous absence of industries, the population explosion is creating heavy pressure on land not only for food clothing etc. but also for employment. Out of the total area about 60% is under hills and plate Aus. Forest constitutes about 36% of the total area. The net area under cultivation during 1977-78 was 2.46 lakhs hectares accounting only 23% of the total area.
Government of Tripura
Government of Tripura